Imperatives of managing the economic security of development companies - Stetsenko, S.; Moholivets, A.; Chynchyk, A.; Kyrylov, I. (Ways to Improve Construction Efficiency, 2022)
The article examines the imperatives of managing the economic security of development companies in the context of the transformation of the economic environment, increasing risks and decreasing predictability of business processes in the field of construction development. It is substantiated that the economic security of such companies is not only a system of protection against external threats, but also a key tool for strategic stability, financial balance and support for investment attractiveness. The article analyzes modern challenges that affect the stability of development activities, in particular: political and regulatory instability, fluctuations in the capital market, inflationary processes, logistics failures and resource shortages. A conceptual vision of economic security as a multi-level system is formulated, including financial, investment, legal, personnel, information and operational components. The feasibility of using risk-oriented management models based on systematic monitoring of critical indicators, digital analytics and scenario modeling of threats is substantiated. Particular attention is paid to the role of digital tools — ERP systems, BIM modeling, project management systems (PMS), as well as blockchain and artificial intelligence technologies — in ensuring transparency, controllability and predictability of development processes. As a result of the study, an author’s model of an integrated economic security management system for a development company was proposed, which allows increasing the efficiency of risk identification, optimizing internal processes, protecting critical assets and ensuring the stability of the implementation of investment and construction projects in the medium and long term. The conclusion was made about the need to develop regulatory and methodological support and implement economic and legal mechanisms to support economic security in development at the institutional level.